2022
DOI: 10.2147/clep.s357927
|View full text |Cite
|
Sign up to set email alerts
|

The Doctors’ Effect on Patients’ Physical Health Outcomes Beyond the Intervention: A Methodological Review

Abstract: Background Previous research suggests that when a treatment is delivered, patients’ outcomes may vary systematically by medical practitioner. Objective To conduct a methodological review of studies reporting on the effect of doctors on patients’ physical health outcomes and to provide recommendations on how this effect could be measured and reported in a consistent and appropriate way. Methods The data source was 79 included studies and rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Doctors with exceptional communication qualities, excellent diagnostic abilities, or outstanding treatment success were equally valued by the respondents and the respondents had no consensus on how many qualities are needed to be exceptional. For our previous systematic reviews, we operationally defined an exceptionally good doctor as one who has exceptionally good patient physical health outcomes [ [5] , [6] , [7] ]. Conversely, our survey respondents took a much broader view on their opinions and experiences of exceptionally good doctors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doctors with exceptional communication qualities, excellent diagnostic abilities, or outstanding treatment success were equally valued by the respondents and the respondents had no consensus on how many qualities are needed to be exceptional. For our previous systematic reviews, we operationally defined an exceptionally good doctor as one who has exceptionally good patient physical health outcomes [ [5] , [6] , [7] ]. Conversely, our survey respondents took a much broader view on their opinions and experiences of exceptionally good doctors.…”
Section: Discussionmentioning
confidence: 99%
“…To discern whether doctors' have varying ability in treating patients, the authors conducted a systematic review [ [5] , [6] , [7] ] screening over 10,000 studies and found that doctors have an effect on patients’ physical health, varying from the negligible to substantial, depending on the intervention and outcome measured. This effect persists after all known variables, such as doctor demographics and experience, hospital effects, patient demographics, and risk factors have been accounted for [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this study have previously systematically reviewed studies reporting doctors' effects on patients' physical health outcomes beyond those explained by known factors such as doctor experience. 33,47,48 Results showed there are doctors that have exceptional patient outcomes that are not explained by known factors, suggesting exceptional doctors exist. The aim of the present study is to qualitatively study the opinions of medical doctors on their experiences of exceptional doctors and what made these doctors exceptionally good.…”
Section: The Present Studymentioning
confidence: 99%
“…Many available RCTs and cohort studies could be reanalyzed to address and estimate the doctors’ effects. 81 When grading doctors by patients’ physical health outcomes, it is at times possible to identify positive and negative outliers whose confidence interval ranges wholly above or below the average performance. Therefore, it can matter greatly which doctor is chosen.…”
Section: Discussionmentioning
confidence: 99%